Escape from the Twin Towers - Messner, Kate; McMorris, Kelley (New York : Scholastic Press, 2020)
Ranger the time-travelling Golden retriever was trained for search-and-rescue and even though he did not pass the tests he has used his training on his many trips to help people caught up in disasters; now he has arrived at the World Trade Center on the morning of September 11, 2001 just as the first plane hits, and he must rescue fifth-graders Risha and Max who are trapped in the wreckage, guide them to safety, and hopefully reunite them with Risha's mother who works on the ninety-first floor.
Includes bibliographical references.
4.1
3-6
570L
Keywords: World Trade Center (New York, N.Y. : 1970-2001) -- Juvenile fiction; Golden retriever -- Juvenile fiction; Time travel -- Juvenile fiction; September 11 Terrorist Attacks, 2001 -- Juvenile fiction; Missing persons -- Juvenile fiction; World Trade Center (New York, N.Y. : 1970-2001) -- Fiction; Golden retriever -- Fiction; Dogs -- Fiction; Time travel -- Fiction; September 11 Terrorist Attacks, 2001 -- Fiction; Rescue work -- Fiction; Missing persons -- Fiction; New York (N.Y.) -- Fiction; Time-travel fiction